Targeting the STAT3 signaling pathway in cancer: Role of synthetic and natural inhibitors - Siveen, K.; Sikka, S.; Surana, R.; Dai, X.; Zhang, J.; Kumar, Alan Prem; Tan, B.; Sethi, G.; Bishayee, A. (Elsevier BV, 2013)
Signal transducers and activators of transcription (STATs) comprise a family of cytoplasmic transcription factors that mediate intracellular signaling that is usually generated at cell surface receptors and thereby transmit it to the nucleus. Numerous studies have demonstrated constitutive activation of STAT3 in a wide variety of human tumors, including hematological malignancies (leukemias, lymphomas, and multiple myeloma) as well as diverse solid tumors (such as head and neck, breast, lung, gastric, hepatocellular, colorectal and prostate cancers). There is strong evidence to suggest that aberrant STAT3 signaling promotes initiation and progression of human cancers by either inhibiting apoptosis or inducing cell proliferation, angiogenesis, invasion, and metastasis. Suppression of STAT3 activation results in the induction of apoptosis in tumor cells, and accordingly its pharma- cologicalmodulation by tyrosine kinase inhibitors, antisense oligonucleotides, decoy nucleotides, dominant neg-ative proteins, RNA interference and chemopreventive agents have been employed to suppress the proliferation of various human cancer cells in culture and tumorigenicity in vivo. However, the identification and development of novel drugs that can target deregulated STAT3 activation effectively remains an important scientific and clinicalchallenge. This review presents the evidence for critical roles of STAT3 in oncogenesis and discusses the potential for development of novel cancer therapies based on mechanistic understanding of STAT3 signaling cascade.